Evaluation of Maternal and Perinatal Outcomes of Induction in Borderline Oligohydramnios at Term - SETU RATHOD; SUNIL KUMAR SAMAL (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Oligohydramnios is described as decreased amniotic fluid volume relative to gestational age. Semiquantitatively it is described using the Amniotic Fluid Index (AFI) which is calculated by adding the depth in centimetres of the largest vertical pocket in each of four equal uterine quadrants. AFI less than or equal to 5 cm is defined as oligohydramnios. A Borderline Oligohydramnios (BO) is defined as AFI 5.1-8 cm. Aim: To assess the maternal and perinatal outcome of induction in borderline oligohydramnios cases at term. Materials and Methods: This is a retrospective observational study done from December 2015 to November 2016 in Mahatma Gandhi Medical College and Research Institute, Puducherry, India. Fifty cases of BO with AFI 5.1 cm - 8 cm taken as case and another 50 cases of Normal Liquor (NL) with AFI 8.1 cm 18 cm taken as control. Data was collected and analysed by SPSS software version 20.0 For qualitative data, the χ2 -test or Fisher’s-exact test were used and for continuous variables, the t-test was used. Results: Cases and controls were matched in baseline parameters. More number of cases were found with meconium stained liquor during labour which is statistically significant (p<0.05). Otherwise there were no statistical significant difference between cases and controls in maternal and perinatal outcome. Conclusion: Induction of labour in cases with BO cases compared to those with NL at term did not show very statistically significant difference in terms of induction to delivery interval and neonatal outcome.